Dystocia Due to Hydrocephalic Teratology through Mutational Operations in a Cross-Bred Jersey Cow - Bhathra, Nagarajakumar Revathy; Gupta, Chhavi; Prabaharan, Vaiyapuri; Ganesan, Ajevar; Sabarinathan, Akambaram (The Indian Journal of Animal Reproduction, 2025)
Hydrocephalus is a dropsical condition with the accu mulation of fluid in cranium as a result of an imbalance  between the formation and drainage of cerebrospinal fluid  (CSF) either in the ventricular system or subarachnoid  space characterized by marked enlargement of the cra nium (Noakes et al., 2009). The condition may be caused  by environmental influences during fetal development or  genetic predisposition of simple autosomal recessive gene  with incomplete penetrance (Jackson, 2004) or acquired  by in-utero viral infections such as Bovine viral diarrhoea  (Agerholm et al., 2015). Other predisposing factors for  this malformation may include deficiency of vitamin-A  or any other brain lesions that may cause a disturbance in  the cerebrospinal fluid dynamics (Ferris et al., 2011). Jubb  and Kennedy (1970) stated that congenital hydrocephalus  is known to be inherited in cattle and exacerbated its man ifestation by a coexisting hypovitaminosis-A. Death of the fetus is due to pressure on vital centres of the brain. The  frontal, temporal and parietal bones are usually involved  becoming deformed, separated and thin resulting in  improper sculpturing of cranial vault  (Purohit et al., 2012). The condition does not affect foetal  development but may result in death of the foetus at birth  or soon after birth. The present case reports successful  per-vaginal delivery of hydrocephalus foetus after relieving  fluid from enlarged head through mutational operations.
Keywords: Intermittent Contractions; Hydrocephalus; Anterior longitudinal; Retropulsion